Pathogenic PHIP Variants are Variably Associated With CAKUT - Jonathan de Fallois; Tobias Sieckmann; Ria Schönauer; Friederike Petzold; Johannes Münch; Melissa Pauly; Georgia Vasileiou; Christin Findeisen; Antje Kampmeier; Alma Kuechler; André Reis; Eva Decker; et al. (Kidney International Reports)
Introduction: Congenital anomalies of the kidney and urinary tract (CAKUT) represent the most common cause of chronic kidney disease in children. Although only 20% of cases can be genetically explained, the majority remain without an identified underlying etiology. The neurodevelopmental disorder Chung-Jansen syndrome (CHUJANS) is caused by haploinsufficiency of Pleckstrin homology domain-interacting protein (PHIP) and was previously associated with genital malformations. Anecdotal coincidence of CHUJANS and CAKUT prompted us to investigate whether urorenal malformations are part of the phenotypic spectrum of CHUJANS. Methods: Analysis of existing CHUJANS and CAKUT cohorts, consulting matchmaking platforms, and systematic literature review to look for additional patients with both CHUJANS and CAKUT. Prenatal expression studies in murine and human renal tissues to investigate the role for PHIP in kidney development. Results: We identified 4 novel and 8 published cases, indicating variable expressivity with a urorenogenital trait frequency of 5% to 35%. The prenatal expression studies supported a role for PHIP in normal kidney and urinary tract development. Conclusion: Pathogenic PHIP gene variants should be considered as causative in patients with syndromal CAKUT. Conversely, patients with CHUJANS should be clinically evaluated for urorenogenital manifestations. Because neurodevelopmental disorders are often associated with kidney phenotypes, an interdisciplinary re-evaluation offers promise in identifying incompletely penetrant kidney associations and uncovering novel molecular mechanisms of disturbed nephrogenesis.